Chronic intermittent hypoxia and the expression of orexin and its receptors in the brains of rats. Issue 1 (January 2014) - Liu, Zilong; Jiang, Liyan; Zhu, Fen; Fu, Cuiping; Lu, Shenyuan; Zhou, Jing; Wu, Xiaodan; Bai, Chunxue; Li, Shanqun
Abstract Chronic intermittent hypoxia (CIH) is the main pathophysiological feature of obstructive sleep apnea (OSA). It destroys the normal sleep rhythm and affects many basic physiological processes, leading to repeated arousal from sleep. Orexin, a very potent arousal neuromodulator found in the brain, has been shown to play a significant role in the promotion and maintenance of arousal. These findings may indicate that orexin participates in the arousal‐promoted processes induced by CIH. However, so far, little is known about alterations in orexin and its receptors during CIH. In the present study, the influence of CIH and re‐oxygenation on the expression of prepro‐orexin (PPO) in the hypothalamus and orexin receptors in the hypothalamus and the medulla of rats were evaluated. The expression of PPO, OX1R, and OX2R mRNA was evaluated by RT‐PCR after the rats had been exposed to intermittent hypoxia (IH) for either 1 week or 5 weeks. The control group was exposed to intermittent air (IA). The results showed the levels of expression of PPO, OX1R, and OX2R mRNA to be significantly higher in the brains of rats exposed to IH for 5 weeks than in the brains of control rats. This effect was reversed by 5 weeks of re‐oxygenation. These findings indicated that CIH could increase the expression of orexin and its receptors in the brain. This may contribute to the sleep fragmentation experienced by patients with OSA, which is induced by repeated arousal.